BCL7C suppresses ovarian cancer growth by inactivating mutant p53. (11th December 2020) - Huang, Canhua; Hao, Qian; Shi, Getao; Zhou, Xiang; Zhang, Yu
Abstract: B-cell CLL/lymphoma 7 protein family member C (BCL7C) located at chromosome 16p11.2 shares partial sequence homology with the other two family members, BCL7A and BCL7B. Its role in cancer remains completely unknown. Here, we report our finding of its tumor-suppressive role in ovarian cancer. Supporting this is that BCL7C is downregulated in human ovarian carcinomas, and its underexpression is associated with unfavorable prognosis of ovarian cancer as well as some other types of human cancers. Also, ectopic BCL7C restrains cell proliferation and invasion of ovarian cancer cells. Consistently, depletion of BCL7C reduces apoptosis and promotes cell proliferation and invasion of these cancer cells. Mechanistically, BCL7C suppresses mutant p53-mediated gene transcription by binding to mutant p53, while knockdown of BCL7C enhances the expression of mutant p53 target genes in ovarian cancer cells. Primary ovarian carcinomas that sustain low levels of BCL7C often show the elevated expression of mutant p53 target genes. In line with these results, BCL7C abrogates mutant p53-induced cell proliferation and invasion, but had no impact on proliferation and invasion of cancer cells with depleted p53 or harboring wild-type p53. Altogether, our results demonstrate that BCL7C can act as a tumor suppressor to prevent ovarian tumorigenesis and progression by counteracting mutant p53 activity.